Comparative effectiveness of exercise-based cardiac rehabilitation for heart failure: a Bayesian network analysis of 44 randomized trials and 5896 patients. (3rd October 2022) - Jiang, L; Wan, R X; Li, J T; Yan, Y
Abstract: Introduction: The prevalence of heart failure (HF) is increasing nowadays. Exercise-based cardiac rehabilitation (CR) reduces mortality and further improves the outcome of patients with HF. However, the effect of different types of CR on HF remains unclear. Data comparing these CR have not been synthesized. Thus, the purpose of this study is to determine the relative efficacy of different types of exercise-based CR for individuals with HF using a Bayesian network meta-analysis. Methods: We followed a pre-specified protocol (PROSPERO: CRD42021278351). We conducted a systematic literature review of any randomized controlled trials which evaluated exercise-based CR for patients with HF. Databases including Embase, Medline, the Cochrane Central Register of Controlled Trials, and Web of Science were screened up to 31 December 2021. The primary outcomes focus on functional capacity (peak oxygen uptake and 6-minute walk distance) and health-related quality of life (hr-QOL). The main analysis was complemented by network subanalysis, standard pairwise comparisons, and subgroup and sensitivity analyses. The pooled estimates were quantified as mean differences (MD) or standardized mean difference (SMD)where appropriate, at 95% confidence intervals (CI). Results: We identified 44 randomized controlled trials with a total of 5896 HF participants. Among 23 studies that compared exercise-based CR and usual care, participants in center-based CR (CBCR) had improvement of peak oxygen uptake (MD: 2.30 mL/kg per minute; 95% CI, 0.43–4.40) and 6-minute walk distance (MD: 33 meters; 95% CI, 11.00–58.00).18 studies that compared exercise-based CR with usual care showed that CBCR and cardiac telerehabilitation (CTR) had greater improvements in hr-QOL (SMD: −0.38; 95% CI, −0.49 to −0.15 and SMD: −0.18, 95% CI, −0.36 to −0.00 respectively). Treatment ranking indicated CTR has the highest probability (46.0%, 50.2%) of being the most effective CR for peak oxygen uptake and hr-QOL elevation respectively. CBCR was similarly indicated as the most effective treatment for 6-min walk distance (38.7%). Conclusion: Exercise-based CR programs provide broader cardiovascular benefits compared with UC. CBCR significantly improved functional capacity. CBCR and CTR have favorable effects on hr-QOL. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): China Scholarship Council